Influence of gamma irradiation on the characteristic and dielectric properties of XLPE / Nano-silica composite - Soliman A. Said, El-Sayed; R. Elsharkawy, Eltohamy.; Abdul El-Aziz Othman, El Saeed; Redaezz-Eldin, Mohamed; El-Kattan, Walaaabd-Elmonem (International Journal of Engineering and Technology, 2019)
This paper investigates silica nanomaterial-based on cross-linked polyethylene (XLPE) for enhancing the electrical and mechanical properties in the insulation of power cables. The electrical cable insulation properties have been improved by adding a certain amount of spherical nanoparticles of fumed silica in a matrix of the polymer. Also, this paper has studied the impact of aging on XLPE and XLPE/SiO2 cable electrical parameters. The morphology of composite XLPE/SiO2 nanocomposites was characterized by scanning electron microscopy and the accelerated aging experiment was performed by 60Co gamma-ray source. It found that XLPE/SiO2 nanocomposites had better dielectric and mechanical properties; XLPE with 1 % Nano silica was found the optimal loading fraction where the breakdown voltage of the Nano silica samples is greater than that of the XLPE sample during low-dose gamma irradiation, while the breakdown voltage of both is reduced at high doses of radiation. Furthermore, electrical capacitance and dielectric constant were decreased by about 54% and 52%, respectively, over the unfilled XLPE at 50 KGy compared to XLPE/SiO2 at optimal loading fraction. Although the tensile strength for 1% XLPE/SiO2 decrease with increasing the radiation dose the elongation increase and give more elasticity and stability in the mechanical properties.Â Â